Information system management - Diwan, Parag (New Delhi Pentagon Press, 2001)
The present book is designed to serve as a reference text for managers specializing in Finance,Marketing Internatonal Business,Human Relation and other areas who wish to harness the power of IT.This book would also serve as the basic course for students w
Keywords: Information resources management; Management information systems